Assessment of Risk Factors For Patients With Thyroid Cancer in Mosul Teaching Hospitals - Taha Hassan Taha Alsaiq; Emad Elias Khaleel Albrimami (College of Nursing,University of Mosul, 2014)
Background and Objectives: Thyroid cancer is the most common endocrine malignancy. Several risk factors were found to play a role in thyroid cancer. The aim of the study was to identify risk factors for thyroid cancer in Mosul city and to assess the relationship between some types of food and thyroid cancer. Materials and Methods: The Non-experimental Quantitative design (a Case - Control approach) was used in this study. The study was conducted at AL-Jamhori Teaching Hospital, Al-Salam Teaching Hospital, and Nuclear Medicine and Oncology Hospital in Mosul city. The period from 18th. October, 2012 to 20th, August, 2013. A formal consent was taken from all participants (case group and control group) in questionnaire . A non probability purposive sample was selected that consisted (172) clients divided into two groups, a case group (86) clients with thyroid cancer and a control group (86) clients without goiter and thyroid cancer. Results: According to the age, the highest percentage was in the age group (50-59 years),constituted (34%)for the case group. The majority of the case group are female who were accounted (78.0%) female to male ratio 4:1. The incidence of differentiated thyroid carcinoma according to histopathology was increased for women compared with men specially papillary thyroid carcinoma. Conclusion: The statistical analysis shows that there are significant relationship in previous history for goiter, family history for thyroid cancer, and exposure to radio active iodine items with respect to the risk factors of thyroid cancer. Keywords: Assessment, Risk Factors, Thyroid Cancer.